2001
DOI: 10.1002/dev.1006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ectopias and their cortical location on several measures of learning in BXSB mice

Abstract: About half of BXSB/MpJ-Yaa mice have ectopias, which are misplaced clusters of neurons located in layer I of cortex. This study replicated several previous findings showing that there are learning differences between mice with ectopias and those without. In addition, we had sufficient numbers of ectopic mice to investigate if ectopics learned differently depending on the cortical location of the ectopia(s). Mice with at least one ectopia located in prefrontal cortex were initially impaired in learning the Morr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…MLH in mice are indistinguishable from heterotopia observed in humans. Consistent with a model of altered brain function associated with MLH, mice with heterotopia have impaired learning of spatial and nonspatial memory tasks [24,25,26,27,28]. Mice with MLH also exhibit sensory processing deficits demonstrated by both behavioral measures in sensory discrimination tasks as well as with sensory-evoked potential recording [29,30,31,32].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…MLH in mice are indistinguishable from heterotopia observed in humans. Consistent with a model of altered brain function associated with MLH, mice with heterotopia have impaired learning of spatial and nonspatial memory tasks [24,25,26,27,28]. Mice with MLH also exhibit sensory processing deficits demonstrated by both behavioral measures in sensory discrimination tasks as well as with sensory-evoked potential recording [29,30,31,32].…”
Section: Introductionmentioning
confidence: 74%
“…Taken together, these data indicate that there exists a diverse complement of neurons in MLH and suggest that these neurons may participate in a synaptic network that contributes to the cortical dysfunction manifested by patients with MLH. Consistent with this hypothesis, mice with MLH have impaired learning of spatial and nonspatial memory tasks [24,25,26,27,28], sensory processing deficits [29,30,31,32] and increased seizure susceptibility [34]. Future studies should be aimed at characterizing the synaptic circuitry and physiological profile of neurons in C57BL/6J mice with MLH, toward gaining a better understanding of how heterotopia cause cortical dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…How neocortical malformations contribute to intrastrain variability as well as interstrain differences in these studies is unknown. However, results from behavioral and physiological studies in mice with molecular layer heterotopia are clear, indicating changes in cognitive function (Hyde et al 2000(Hyde et al , 2001(Hyde et al , 2002 and sensory processing (Frenkel et al 2000;Peiffer et al 2001). These results emphasize the importance of histological examination of neocortical tissue from inbred mice used in strain surveys.…”
Section: Transcriptional Diversity and Density In Neocortical Malformmentioning
confidence: 81%
“…Interestingly, Denenberg and colleagues performed a comprehensive series of studies showing that "ectopic" mice – those with spontaneously occurring neuronal migration disorders (ectopic collections of neurons in the molecular layer) – also exhibit significant anomalies when compared to non-ectopic littermates on memory tasks. For example, ectopic BXSB/MpJ mice – a strain in which about 40–60% of mice exhibit spontaneous ectopias in and around the prefrontal cortex – display robust and replicable deficits in a water-escape version of the radial arm maze when compared to non-ectopic littermates [ 41 , 42 ]. Additional studies found that ectopic BXSB/MpJ mice exhibit deficits on a delayed match-to-sample version of the Morris water maze (which depends heavily on within-session or working memory [ 43 ]), and also make more working memory errors in an inverted version of the Lashley III maze [ 39 ].…”
Section: Discussionmentioning
confidence: 99%